The Real-Life Effectiveness of Palivizumab for Reducing Hospital Admissions for Respiratory Syncytial Virus in Infants Residing in Nunavut. Issue 3 (2014) - Banerji, Anna; Panzov, Vladimir; Young, Michael; Lee, Bonita E; Mamdani, Muhammad; Giles, B Louise; Dennis, Marguerite; Morel, Johanne; Bisson, Danny; Paes, Bosco A; Hui, Charles; Mahony, Jim
Abstract : BACKGROUND/OBJECTIVE: Nunavut has the highest hospitalization rates for respiratory syncytial virus (RSV) worldwide, with rates of 166 per 1000 live births per year <1 year of age. Palivizumab was implemented in Nunavut primarily for premature infants, or those with hemodynamically significant cardiac or chronic lung disease; however, the effectiveness of the program is unknown. The objective of the present multisite, hospital-based surveillance study was to estimate the effectiveness of palivizumab in infants <6 months of age in Nunavut for the 2009 and 2010 RSV seasons. METHODS: Infants identified as palivizumab candidates who were <6 months of age were compared with all admissions for lower respiratory tract infection through multisite, hospital-based surveillance documenting the adequacy of palivizumab prophylaxis, admission for lower respiratory tract infection and the results of RSV testing. The OR for RSV admission in unprophylaxed infants was compared with those who were prophylaxed, and the effectiveness of palivizumab was estimated. RESULTS: Within the study cohort (n=101) during the two RSV seasons, five of the 10 eligible infants who did not receive adequate prophylaxis were admitted with RSV while two of the 91 infants <6 months of age eligible for palivizumab who were adequately prophylaxed were hospitalized with RSV (OR 22.3 [95% CI 3.8 to 130]; P=0.0005). The estimated effectiveness of palivizumab for the cohort was as high as 96%. Eight eligible infants were missed by the program and did not receive prophylaxis. CONCLUSION: Palivizumab was highly effective in reducing hospitalizations due to RSV infection in Nunavut. Further efforts need to be made to ensure that all eligible infants are identified.